Codeine induced hematological, hepatic alterations, lung and brain damage in mice - Bernard Omokheshi Adele; Adeyinka Joseph Alonge; Elsie Olufunke Adewoye (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2022)
Codeine, an opiate derivate, which induces pleasure and euphoria in users, is contained in many OTC cough syrups as dextromethorphan. In 2011, its abuse has been reported in Nigeria from consumption of codeine-based cough syrup such as Benylin containing codeine syrup (BCS). Thereafter, the neurobehavioural alteration was reported with BCS in mice. 45 Swiss male mice (20 g -25 g) were grouped into control, low dose-(10.95 ml/kg BCS) and High dose-(21.90 ml/kg of BCS). BCS was given orally above the therapeutic dose for 4weeks. Blood samples were collected after 7 and 28days under mild ether anesthesia into plain and heparinized bottles to assess hematological indices, serum creatinine level, and activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Thereafter, the brain, lung, and liver were excised and processed for brain protein level and histopathological observation. Data were analyzed using Two-way ANOVA at P < 0.05. At both doses, BCS reduced hemoglobin concentration (10.56; 21.69%), lymphocyte count (10.54; 29.22%) and brain protein level (4.86±0.81; 4.86 ± 0.80 vs 9.20 ± 0.61 g/l) while white blood cell count (20.47; 46.08%), serum creatinine level (5.36; 18.75%), AST (26.31; 32.77%) and ALT (22.90; 36.70%) activities were increased compared to control. Histology shows marked necrosis and chronic infiltration by inflammatory cells in the brain, liver, and lung. Acute and chronic treatment of mice with Benylin with codeine resulted in significant alterations in blood and vital body organs such as kidney, liver, lung, and brain in a dose-dependent manner.